The inflammatory potential of the diet in childhood is associated with cardiometabolic risk in adolescence/young adulthood in the ALSPAC birth cohort. - Buckland, Genevieve; Northstone, Kate; Emmett, Pauline M.; Taylor, Caroline M. (European Journal of Nutrition, 2022)
Purpose: This study examined the association between a Dietary Inflammatory Score adapted for children (cDIS) and Cardiometabolic Risk (CMR) score in adolescence/early adulthood in the Avon Longitudinal Study of Parents and Children (ALSPAC). Methods: The cDIS was calculated at 7, 10 and 13 years using diet diary data. Anthropometric and biochemical data at 17 (N = 1937) and 24 (N = 1957) years were used to calculate CMR scores at each age [mean sex-specific z-scores from triacylglycerol, HDL-cholesterol, LDL-cholesterol, mean arterial blood pressure (MAP), homeostatic model assessment of insulin resistance (HOMA-IR) and fat-mass index (FMI)]. Multivariable linear regression models examined associations between cDIS at 7, 10 and 13 years and a continuous CMR z-score and individual CMR markers at 17 and 24 years. Results: In fully adjusted models, a higher cDIS (more pro-inflammatory diet) at 7 years was associated with an increase in CMR z-score at 17 years (β 0.19; 95% CI 0.03–0.35 for third versus first cDIS tertile) and at 24 years (β 0.28; 95% CI 0.11,0.44 for third versus first cDIS tertile). There was a weak association between a higher cDIS at 10 years and an increase in CMR z-score at 17 years (β 0.16; 95% CI − 0.003, 0.32 for third versus first cDIS tertile). No other clear associations were evident. FMI, MAP and HOMA-IR were the main CMR factors contributing to these associations. Conclusion: A more pro-inflammatory diet during childhood was associated with a worse cardiometabolic profile in late adolescence/early adulthood. A childhood diet abundant in nutrients with anti-inflammatory properties could help reduce development of CMR factors.